2020
DOI: 10.1080/23311975.2020.1771076
|View full text |Cite
|
Sign up to set email alerts
|

The effect of audit fees on disclosure quality in Jordan

Abstract: Disclosure quality is a matter of great importance in the accounting literature. This study examines the effect of audit fees, audit firm size and audit opinion on the quality of disclosures. It focuses on a sample of low-quality financial statements in Jordan that have been reported as breaches by the Jordanian Securities Commission (JSC). Data were collected from the financial statements of the manufacturing and services companies listed on the Amman Stock Exchange (ASE) during the period 2009 to 2016. The l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 80 publications
1
10
0
Order By: Relevance
“…Moreover, higher audit fees can indicate the restatement of financial reports and can also be used to assess the quality of financial reporting of a firm. Therefore, the audit fees ratio index has also been used as a determinant of financial reporting disclosure quality, consistent with Tang (2008), Bala et al (2018) and Shakhatreh et al (2020). Lantto and Shalstrὂm (2009) used key financial indicators as proxy indicators to measure a firm's financial reporting disclosure quality.…”
Section: Ifrs Compliance As a Measure Of Financial Reporting Disclosure Qualitymentioning
confidence: 92%
“…Moreover, higher audit fees can indicate the restatement of financial reports and can also be used to assess the quality of financial reporting of a firm. Therefore, the audit fees ratio index has also been used as a determinant of financial reporting disclosure quality, consistent with Tang (2008), Bala et al (2018) and Shakhatreh et al (2020). Lantto and Shalstrὂm (2009) used key financial indicators as proxy indicators to measure a firm's financial reporting disclosure quality.…”
Section: Ifrs Compliance As a Measure Of Financial Reporting Disclosure Qualitymentioning
confidence: 92%
“…Audit resource costs are related to the number of audit efforts the auditors took in auditing and the risk premium is compensation for risk-taking. Shakhatreh, et al (2020) suggested that in the provision of audit services, independent external auditors are paid fees for their services rendered. The level of fees paid relates to the efforts of the external auditors.…”
Section: Concept Of Audit Firm Characteristicsmentioning
confidence: 99%
“…Defond et al (2018) stated that external audit firm expertise is one of the qualities in big audit firms' services. Shakhatreh, et al (2020) noted that the skill and knowledge factors will determine auditor switching by the firm so that the company prefers big audit firms. A study conducted by Ugwu (2020) found a positive and not significant association between audit firm size and auditor switching in Nigeria.…”
Section: Audit Firm Sizementioning
confidence: 99%
“…In this study, audit fee is taken as a measure of audit risk. Khan and Abdul Subhan (2019) argue that a high audit fee is an indication of high audit quality due to extended audit hours and expert audit staff to conduct more detailed investigation and Shakhatreh et al (2020) find that audit fee has a significant effect on disclosure quality. The audit fee is higher for firms that undertook RPTs and internal audit function have a moderating effect on the relationship between RPTs and audit fee (Al-dhamari et al, 2018).…”
Section: Literature Review and Development Of Hypothesesmentioning
confidence: 99%